Preparation and Characterization of Novel Low‐Temperature/pH Dual‐Responsive Poly(N‐isopropylacrylamide‐co‐1H‐benzimidazolyl‐ethyl acrylate) Copolymers. Issue 11 (2nd May 2019) - Zhang, Shu‐Gui; Ju, Xiao‐Jie; Zhou, Xing‐Long; Pu, Xing‐Qun; Peng, Han‐Yu; Wang, Wei; Xie, Rui; Liu, Zhuang; Chu, Liang‐Yin
Abstract: Stimuli‐responsive polymers in response to both low temperature and pH are of great potential for designing drug carriers to obtain a better therapeutic effect during cryotherapy of tumors. In this work, novel low‐temperature and pH dual‐responsive poly( N ‐isopropylacrylamide‐ co ‐1 H ‐benzimidazolyl‐ethyl acrylate) (PNBM) linear copolymers are developed, which can undergo stretching/shrinking conformational transition at low temperature and mildly acidic conditions. The dual‐responsive properties of PNBM copolymers can be affected and regulated by the host–guest inclusion action between benzimidazole and hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD) molecules. The critical response temperature of the copolymers can be flexibly adjusted when the benzimidazole groups in copolymer chains are captured by HP‐β‐CD. And the PNBM copolymers present a pH‐responsive stretching‐to‐shrinking‐to‐stretching conformational transition in a narrow pH range in HP‐β‐CD solution. The results provide valuable guidance for designing and applying PNBM‐based smart materials in biomedical applications. Abstract : Temperature and pH dual‐responsive copolymers are successfully developed by introducing benzimidazole groups into poly( N ‐isopropylacrylamide) polymers. These copolymers can undergo conformational transition between the stretching state and the shrinking state at low temperatures and mildly acidic pH. Hydroxypropyl‐β‐cyclodextrin can capture hydrophobic benzimidazole groups in copolymer chains to form inclusion complexes, which can affect and adjust the dual‐responsive properties of the copolymers.